Elections - Courtney, John C. (John Childs), 1936- (Canadian democratic audit., 2004)
Open and competitive elections governed by widely accepted rules and procedures are essential to any political system's legitimacy. This volume, by eminent political scientist John Courtney, assesses the history and development of five "building blocks" of Canada's electoral regime: the franchise, electoral districts, voter registration, election machinery, and plurality voting. Arguing that on balance, Canada's electoral regime can be judged to be truly democratic, the book demonstrates the vast improvements that have been made over the years: the right to vote is generously interpreted; the process of redrawing electoral districts is no longer in the hands of elected officials; voter registration lists include all but a small share of eligible voters; and those who manage and supervise elections on behalf of all citizens are honest and trustworthy officials. Using the recent push for the reform of the plurality vote system as one example, it also examines why certain electoral institutions have been amenable to reform and others have not. In a democracy such as Canada's, it is important for citizens to understand the most essential parts of their electoral system. This book is designed with this goal in mind. A concise analysis of complex issues, it presents reasoned judgments on links between electoral institutions and representative democracy, and is an ideal primer for undergraduate students, journalists, politicians, and anyone interested the current state of Canadian democracy.